Weather shocks, credit and production efficiency of rice farmers in Vietnam - Thanh Tung Nguyen; Nguyen-Trung-Thanh; Ulrike Grote (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2020)
Enhancement of rice production efficiency in developing countries is important to improve the livelihoods of farmers and to ensure global food security for a growing population. Despite significant progress in recent decades, rice production in these countries is facing multiple challenges from climate change, land degradation, to the increasing competition for land and labor from urbanization and industrialization. Given that rice farmers in Vietnam often suffer from extreme weather events and lack of access to credit, our study aims to (i) investigate the impact of weather shocks and credit on the rice production efficiency, and to (ii) examine the role of credit in mitigating the impact of weather shocks. We find that weather shocks, land fragmentation and the migration of household members are the major sources of inefficiency. Meanwhile, livestock, farm mechanization and education level are positive factors for rice production efficiency. In addition, our results show that access to credit plays a significant role in mitigating the negative impact of weather shocks. Our studies call for more assistance and support to farmers in mitigating the severe effect of weather shocks, in particular, via the promotion of credit market. In addition, the encouragement of farm mechanization, land defragmentation, livestock farming and the improvement of rural education should be given a high priority to improve the rice production efficiency.
Keywords: Q12; G50; Q54; 330; weather shocks; Agricultural production efficiency; Credit